Additive negative prognostic value of coronary flow reserve in patients with left bundle branch block without inducible ischemia and without known coronary artery disease. (3rd October 2022) - Boskovic, N; Giga, V; Dedic, S; Ostojic, M; Karadzic, T; Rakocevic, I; Aleksandric, S; Petrovic, O; Tesic, M; Jovanovic, I; Nedeljkovic, I; Banovic, M; et al.
Abstract: Background: Left bundle branch block (LBBB) can be isolated thing, but it is also often associated with underlying coronary artery disease (CAD). Stress echocardiography (SECHO) is widely used as an imaging method for the diagnosis of CAD. However, the diagnostic value of stress echocardiography in patients (pts) with LBBB is limited. Purpose: To evaluate negative prognostic value of coronary flow reserve (CFR) in pts with LBBB without inducible ischemia and without known CAD. Methods: This retrospective study included 224 pts (98, 43.8% male gender, average age 66±11 years) with LBBB and without known CAD. All the pts had negative SECHO test according the Bruce protocol. Risk factors for CAD (diabetes, smoking, hypertension, high cholesterol and positive family history of CAD), Duke treadmill score, functional capacity (Metabolic Equivalents - METs) were recorded in all pts. Out of 224 pts, in 64 (29.5%) coronary flow reserve on the left anterior descending artery was assessed using pulsed Doppler echocardiography with adenosine in a dose of 140μcg/kg/body weight during 3 minutes. As the normal value we took value of CFR ≥2. Median follow up of the pts was 72 months (IQR 56.25–132 months) for the occurrence of MACE (cardiovascular death (CVD), non-fatal myocardial infarction (nfMI), coronary artery bypass graft (CABG) and percutaneous coronary revascularization (PCI). Results: Out of 224 pts, 6 (2.7%) had positive SECHO test, 2 pts (0.9%) had died due to non-cardiac causes and 11 pts (4.9%) were lost to follow up so they were excluded from further analysis. The remaining 204 pts were divided in 2 groups: 1. pts with only negative SECHO (n=144, 68.8%); 2. pts with negative SECHO and normal CFR (n=64, 31.2%). During the follow-up period 22 out of 205 pts (10.7%) had an adverse event (6 CVD, 6 nfMI, 5 CABG, 8 PCI). Between the two groups there was no significant difference in risk factors and parameters of the SECHO test. Pts with CFR had significantly lower rate of MACE compared to the pts with only SECHO test (2, 3.1% vs 20, 14.2%, p=0.018, respectively). Using the Cox regression analysis, univariate predictors of MACE were insulin dependent diabetes (HR 10.851 [95% CI 2.095–56.220], p=0.004), Duke score (HR 0.603 [95% CI 0.414–0.878], p=0.008), and MET (HR 0.393 [95% CI 0.209–0.737], p=0.004). In the multivariate analysis only the insulin dependent diabetes remained an independent predictor of MACE (HR 6.906 [95% CI 1.100–43.363], p=0.039). Using the Kaplan-Meier survival curve we see that the pts with SECHO test and CFR had shorter event-free time compared to the pts with SECHO test (136.3±3.6 months vs 149.8±2.9 months, Log Rank 4.022, p=0.045) (Figure 1). Conclusion: Normal value of CFR has good negative prognostic value in pts with LBBB without inducible ischemia and without known CAD, while pts with insulin dependent diabetes have more pronounced risk for the occurrence of adverse events. Funding Acknowledgement: Type of funding sources: None.